2007
DOI: 10.1073/pnas.0710335105
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity in mice causes changes in immune responses and bone loss manifested by bacterial challenge

Abstract: Obesity has been suggested to be associated with an increased susceptibility to bacterial infection. However, few studies have examined the effect of obesity on the immune response to bacterial infections. In the present study, we investigated the effect of obesity on innate immune responses to Porphyromonas gingivalis infection, an infection strongly associated with periodontitis. Mice with dietinduced obesity (DIO) and lean control C57BL/6 mice were infected orally or systemically with P. gingivalis, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
219
2
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(253 citation statements)
references
References 34 publications
22
219
2
10
Order By: Relevance
“…There is clear evidence demonstrating more severe horizontal bone loss in murine models infected with P. gingivalis and other Gram‐negative bacteria in addition to this ligature placement (Samejima, Ebisu, & Okada, 1990; Amar, Zhou, Shaik‐Dasthagirisaheb, & Leeman, 2007). The combination of ligature placement and P. gingivalis infection also accelerated the destruction of periodontal tissue and bone resorption as compared to ligature placement without P. gingivalis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence demonstrating more severe horizontal bone loss in murine models infected with P. gingivalis and other Gram‐negative bacteria in addition to this ligature placement (Samejima, Ebisu, & Okada, 1990; Amar, Zhou, Shaik‐Dasthagirisaheb, & Leeman, 2007). The combination of ligature placement and P. gingivalis infection also accelerated the destruction of periodontal tissue and bone resorption as compared to ligature placement without P. gingivalis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fat cell size did not determine inflammation; thus, AT morphology is not involved in the release of inflammatory markers (Hoffstedt et al 2010). A recent study on bacterial challenge showed dysregulation in homeostatic networks counteracting inflammation as obesity develops (Amar et al 2007). The authors associated DIO with a form of immune paralysis.…”
Section: Inflammation and Ageing Inflammagingmentioning
confidence: 99%
“…First, immune function is affected by host nutrition, which may greatly affect the outcome of infection (Lazzaro and Little, 2009;Schmid-Hempel, 2011). Host nutrition influences both constitutive and inducible immune function, with consequences for morbidity and mortality (Cunningham-Rundles et al, 2005;Klasing, 2007) (Adams and Hewison, 2008;Amar et al, 2007;Calder, 2006;Cohen et al, 2008;Kelley and Bendich, 1996;Klasing, 2007;Kolb, 1997;Kristan, 2007;Samartin and Chandra, 2000;Sorci and Faivre, 2009). Second, nutrition-based interactions are one of the major sources of microbial benefits to animals (Bäckhed et al, 2005;Douglas, 2010;Hooper et al, 2002;Kau et al, 2011;Topping and Clifton, 2001).…”
Section: Introductionmentioning
confidence: 99%